Fermentasi etanol dari sari buah jambu mete (Anacardium occidentale L) oleh saccharomyces cerevisme fncc 3015 menggunakan amonium sulfat dan urea sebagai sumber nitrogen Ethanol fermentation from cashew juice ( Anacardiu - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The use of ammonium sulphate and urea as cheap nitrogen sources for ethanol fermentation from cashew juice by Saccharomyces cerevisiae FNCC 3015 was studied. Ethanol fermentation was carried out in batch system at room temperature For 24 hours. Fermentation media consisted of cashew juice (13-15% w/v soluble carbohydrate), 0.1% MgSO4.7H20, and ammonium sulphate or urea in the ranges of 0.25-2.0 g/l and 0.1-1.0 g/1 respectively. The use of ammonium sulphate or urea increased the consumption of soluble carbohydrate and biomass production. Ethanol production slightly increased with the increase of added nitrogen sources up to 1.5 g/I ammonium sulphate or 0.4 g/I urea. Addition of ammonium sulphate or urea did not significantly increased ethanol yield. The maximum ethanol yield obtained was only 70% when refering to the theorical yield. Anunonium sulphate and urea could not control pH media. The decrease of pH media during the ethanol fermentation contributed to the decrease in ethanol production.